Oil Shocks and Their Effects on The Effectiveness of Monetary Policy In Targeting Inflation Rates in Algeria During the Period (2000-2019)- An Econometrics Study- - Taher, Djelit; Azeddine, Makhlouf (Dirassat Journal Economic Issue, 2022)
This study aims to evaluate the impact of oil shocks on the effectiveness of monetary policy in targeting inflation rates in Algeria, and for this purpose, an econometric model was constructed for the period 2000-2019 and based on three variables of the oil price as an indicator of oil shocks, of the money supply and of the inflation rate as an indicator of monetary policy. The standard study showed that the great importance of the relative effect on the inflation rate is due to the oil price variable, the slope of the oil price reaching (-0.85%), while the slope of the money supply did not exceed (0.062%). The occurrence of the inflation rate responds to a greater extent to variations in the price of oil, whether short or long term, and this limits the effectiveness of monetary policy to target the inflation rate in Algeria.